2004
DOI: 10.1097/01.ju.0000137659.53129.14
|View full text |Cite
|
Sign up to set email alerts
|

PROSTATE CANCER DETECTION ON URINALYSIS FOR Α METHYLACYL COENZYME a RACEMASE PROTEIN

Abstract: We report the feasibility of a novel, noninvasive, nonprostate specific antigen based molecular approach to detect prostate cancer in voided urine. To our knowledge this is the first report of AMACR protein detection in the urine of patients with prostate cancer. A screening test based on urinary AMACR may develop into a useful adjunct to serum prostate specific antigen and digital rectal examination for identifying men at increased risk for harboring prostate cancer despite negative biopsy. Such a test has po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(53 citation statements)
references
References 13 publications
1
51
0
1
Order By: Relevance
“…Markers were chosen according to previous studies as being either detectable in urine or appropriate for combined models. AMACR, 7,15,16 SPINK1, 5,17 EZH2, 3,6 GOLM1, 5,18 TRPM8 are overexpressed in CaP, 3,6,19,20 while MSMB is prostate specific but underexpressed in cancer. [21][22][23] Only AMACR was a significant predictor of cancer in the univariate analysis.…”
Section: -13mentioning
confidence: 99%
“…Markers were chosen according to previous studies as being either detectable in urine or appropriate for combined models. AMACR, 7,15,16 SPINK1, 5,17 EZH2, 3,6 GOLM1, 5,18 TRPM8 are overexpressed in CaP, 3,6,19,20 while MSMB is prostate specific but underexpressed in cancer. [21][22][23] Only AMACR was a significant predictor of cancer in the univariate analysis.…”
Section: -13mentioning
confidence: 99%
“…Western blot analysis for AMACR was used on voided urine after TRUS and biopsy, showing a 100% sensitivity and 58% specificity for CaP detection in the group of patients with negative biopsy findings. 10 In another study, the quantification of AMACR transcripts normalized to PSA transcripts in prostate secretions was predictive of CaP. 11 On the other hand, AMACR transcripts normalized to PSA were not statistically significant predictors of CaP in a recent multiplex study of urine markers (see below).…”
Section: Advantages and Limitations Of Novel Urine Markersmentioning
confidence: 98%
“…If possible, evaluation of diagnostic tests should be performed in a blinded fashion. Only 7 studies explicitly reported using a blinded design (13,15,19,24,36,39,40 ). One of these studies (40 ) used different urine sampling methods among cases and controls, which may hinder comparability of results.…”
Section: Discussionmentioning
confidence: 99%